2019
DOI: 10.1038/s41598-018-36634-3
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale experiments into the tsunamigenic potential of different iceberg calving mechanisms

Abstract: Mass balance analysis of ice sheets is a key component to understand the effects of global warming. A significant component of ice sheet and shelf mass balance is iceberg calving, which can generate large tsunamis endangering human beings and coastal infrastructure. Such iceberg-tsunamis have reached amplitudes of 50 m and destroyed harbours. Calving icebergs interact with the surrounding water through different mechanisms and we investigate five; A: capsizing, B: gravity-dominated fall, C: buoyancy-dominated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 36 publications
(69 reference statements)
1
32
0
Order By: Relevance
“…A historical example is the earthquake‐tsunami of December 2004 in Southeast Asia, killing more than 283,000 people on the coasts of the Indian Ocean (e.g., Lay et al, 2005). Although many tsunamis are triggered by submarine earthquakes, other mechanisms can also trigger these waves such as meteorite impacts (e.g., Wünnemann & Weiss, 2015), iceberg calvings (e.g., Heller et al, 2019), subaerial and submarine landslides (e.g., Harbitz et al, 2006; Løvholt et al, 2015), or volcanic eruptions (e.g., Paris, 2015). Despite this, tsunami risk assessments and warning systems are mainly structured to deal with earthquake‐tsunamis, which make populations particularly vulnerable to other source mechanisms (Grezio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A historical example is the earthquake‐tsunami of December 2004 in Southeast Asia, killing more than 283,000 people on the coasts of the Indian Ocean (e.g., Lay et al, 2005). Although many tsunamis are triggered by submarine earthquakes, other mechanisms can also trigger these waves such as meteorite impacts (e.g., Wünnemann & Weiss, 2015), iceberg calvings (e.g., Heller et al, 2019), subaerial and submarine landslides (e.g., Harbitz et al, 2006; Løvholt et al, 2015), or volcanic eruptions (e.g., Paris, 2015). Despite this, tsunami risk assessments and warning systems are mainly structured to deal with earthquake‐tsunamis, which make populations particularly vulnerable to other source mechanisms (Grezio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These dynamic changes seem to be related to a general warming of air temperature and water masses around Greenland (Straneo et al, 2013). Several studies have shown a high sensitivity of outlet glaciers to environmental forcings (Holland et al, 2008;Howat et al, 2010;Carr et al, 2017), while the fjord topography is an important control for the dynamic behaviour of the outlet glaciers (Warren, 1991;Catania et al, 2018). However, major limitations in understanding and predicting the dynamics of outlet glaciers remain, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Wave gauges are a very reliable and accurate measurement system to detect and record the motion of water free surfaces. They are standard measurement instruments in tank testing [64] and can also be used under very complex conditions [38,50,59,60,65] as well as near submerged structures [21,22,66,67]. This measurement system correlates the resistance between two parallel rods with the submerged water depth.…”
Section: Copper Tape Resistive Wave Gaugesmentioning
confidence: 99%